KINERJA KEUANGAN SUB SEKTOR BUILDING CONSTRUCTION NON-BUMN SEBELUM DAN SETELAH PRIORITAS INFRASTRUKTUR - Ray Agung Sucika Pratama; Tony Irawan; Raden Dikky Indrawan (Jurnal Proaksi, 2021)
Since 2014 the government has focused on developing national infrastructure as stated in Nawacita and as seen in the significant increase in the infrastructure budget from 2015-2019. However, the increase in the infrastructure budget did not affect the private building construction sub-sector companies' profit. This study aims to measure the financial performance of the private building construction sub-sector and to determine the significance of the differences between financial performance before and after infrastructure becomes the focus of development. Purposive sampling was used within the criteria of a private building construction sub-sector company that publishes annual financial reports for 2011-2019. The period is divided into two, before infrastructure becomes the focus of development (2011 - 2014) and after infrastructure becomes the focus of development (2015 - 2019). Paired sample t-test and financial ratio analysis (FRA) were used to analyze the data. The results show that return on assets and total asset turnover have a significant difference between the period before and after infrastructure becomes the focus of development, while the current ratio and debt to equity ratio are not significantly different. These findings can be useful for company managers who would continue to explore opportunities to provide higher profits. Keywords: financial performance, construction, profitability, solvency